LIKUIDITAS SEBAGAI PEMODERASI PENGARUH PROFITABILITAS DAN STRUKTUR MODAL PADA RETURN SAHAM PERUSAHAAN MANUFAKTUR - Nugraha, Nyoman Aria; Mertha, I Made (E-Jurnal Akuntansi, 2016)
This study aimed to examine the effect of liquidity as a moderating variable profitability and capital structure on stock returns. Independent variables (independent) on the profitability of this study is proxied by the return to total assets (ROA) and a capital structure in proksikan with a debt to equity ratio (DER). The population in this study are all companies that belong to companies listed in the Indonesia Stock Exchange. This study used a technique moderated regression analysis (MRA). Based on the purposive sampling technique used in this study there were 96 companies that meet the criteria of sampling. These results indicate that liquidity is not able to moderate the influence of profitability on stock returns, and liquidity is not able to moderate the effect of capital structure on stock returns.
Keywords: Liquidity (CR), profitability (ROA), Capital Structure (DER), Stock Return.